Contested Actors around the Initiation of a Non-Judicial Settlement Mechanism for Past Gross Human Rights Violations: A Socio-Legal Study of the PPHAM Team - Munif, Abdul (UI Scholars Hub, 2023)
The PPHAM Team (Non-Judicial Resolution of Past Gross Human Rights Violations) was initiated by the Jokowi-Ma'ruf administration as an alternative settlement mechanism for Past Gross Violations of Human Rights through the issuance of Presidential Decree Number 17/2022 (Keppres 17/2022). From this context, the establishment of the policy was criticized and rejected by civil society organizations (CSOs) and the Victims. This was because the PPHAM Team was deemed a measure of State responsibility “hand-washing” and an indication of impunity preservation. Therefore, this study aimed to evaluate the contestation of actor interests among the State, Victims, CSOs, and others, by emphasizing the theoretical framework of transitional justice. This was a socio-legal study coupled with a qualitative approach, where data were obtained through interviews and observation of mass media coverage. The results argued that the initiation of the PPHAM Team was only beneficial to the interests of the State and did not completely address the preferences of the Victims on accountability and truth.